The role of affluence, urbanization, and human capital for sustainable forest management in China: Robust findings from a new method of Fourier cointegration. (12th October 2022) - Yilanci, Veli; Ulucak, Recep; Zhang, Yaoqi; Andreoni, Valeria
Abstract: Affluence and planned urbanization may have a crucial role in conserving forests and decreasing forest footprint with rising awareness and human development. Productivity rise from technological progress is key to facilitating the underlying mechanisms of theoretically expected changes in all those processes. They are seen as an alternative way to transform the current habits into one that is conservative and respectful to the environment while keeping the economic welfare at the same time. By following the theoretical underpinnings of such expectations, this article investigates how the development changes of China have impacted on the forest footprint. In this frame, the study is an attempt to empirically inquire underlying mechanisms of the forest transition hypothesis, which supports the idea that affluence, urbanization, human capital, and productivity can help to save forests. The transition process is depicted by a hump‐shaped curve mostly attributed to the Environmental Kuznets Curve in the literature. The period 1961–2017 is particularly relevant as it precedes and follows the Chinese open‐door policy of the 1980s. This study reaches robust findings and new insights for sustainable forest management. Results show that income growth did not contribute to reducing the forest footprint, as the forest footprint has increased with income rises. On the contrary, urbanization, human capital, and total factor productivity have reduced the forest footprint. Based on the evidence provided, policymakers should devote increasing attention to education that serves human capital formation, and efficiency gains for sustainable forestry simultaneously.